2007
DOI: 10.1542/peds.2006-0529
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Heparin Versus Placebo Infusion to Prolong the Usability of Peripherally Placed Percutaneous Central Venous Catheters (PCVCs) in Neonates: The HIP (Heparin Infusion for PCVC) Study

Abstract: Heparin infusion prolonged the duration of peripherally inserted central venous catheter usability, which permitted a higher percentage of neonates to complete therapy without increasing adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 28 publications
4
81
0
4
Order By: Relevance
“…These include catheter diameter (gauge), location of catheter tip, fluid infusion rate, dwell time, length of catheter outside the skin and precipitation of calcium and phosphate salts within the tubing. [4][5][6]8,15,16 Although the concentration of heparin used in the first epoch of this study (0.25 to 0.5 units ml À1 ) is low, the dose (0.5 to 2 units kg À1 per h) is comparable to recent reports using 'low-dose' (0.5 units kg À1 per h) heparin. 4,5 Compared with reports by Uslu et al 4 and Shah et al, 5 however, the complication rates observed in the cohorts in both the epochs of this study were lower, and removal of heparin from continuous infusions did not result in an increased rate of occlusion or a decreased duration of use.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…These include catheter diameter (gauge), location of catheter tip, fluid infusion rate, dwell time, length of catheter outside the skin and precipitation of calcium and phosphate salts within the tubing. [4][5][6]8,15,16 Although the concentration of heparin used in the first epoch of this study (0.25 to 0.5 units ml À1 ) is low, the dose (0.5 to 2 units kg À1 per h) is comparable to recent reports using 'low-dose' (0.5 units kg À1 per h) heparin. 4,5 Compared with reports by Uslu et al 4 and Shah et al, 5 however, the complication rates observed in the cohorts in both the epochs of this study were lower, and removal of heparin from continuous infusions did not result in an increased rate of occlusion or a decreased duration of use.…”
Section: Discussionsupporting
confidence: 55%
“…1 However, complications such as occlusion, phlebitis, infection, accidental dislodgement, extravasation and leakage of fluid at catheter junctions proximal to the site of insertion occur with PICCs. [2][3][4][5][6] The identification of factors that are associated with these complications is important for patient safety and as quality improvement initiatives.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,11 Among the infectious complications, the incidence of catheterrelated sepsis with positive blood culture was lower than that reported in other studies in newborns. 2,4,[12][13][14][15] A possible explanation for this low incidence is that the indication for catheter placement in 12 cases was a previous episode of nosocomial sepsis requiring antimicrobial treatment and hemodynamic support and excluding the diagnosis of sepsis unless a different microorganism was detected in blood cultures. Positive catheter tip colonization was also in the low range of published data.…”
Section: Discussionmentioning
confidence: 99%